2022
DOI: 10.1002/anie.202214812
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed 1,2‐Dicarbonylative Cyclization of Alkenes with Alkyl Bromides via Radical Cascade Process

Abstract: Herein, we developed a new procedure on 1,2dicarbonylative cyclization of 4-aryl-1-butenes with alkyl bromides. Using simple copper catalyst, two molecules of carbon monoxide were introduced into the double bond with the formation of four new CÀ C bonds and a new ring. Various α-tetralones and 2,3-dihydroquinolin-4-ones were formed in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Soon after, our group reported a second case of copper-catalyzed carbonylation of alkyl bromides. 14 In this copper-catalyzed 1,2-dicarbonyaltive cyclization system (Scheme 3a), 4-aryl-1-butenes and alkyl bromides constructed a series of α-tetralone and 2,3-dihydroquinolin-4-one through a radical cascade process, constructing four new C–C bonds, and introducing two carbonyl groups and a ring. This reaction has a wide substrate scope and yields the product in moderate to good yields.…”
Section: Carbonylation Reaction Of Alkyl Bromidesmentioning
confidence: 99%
“…Soon after, our group reported a second case of copper-catalyzed carbonylation of alkyl bromides. 14 In this copper-catalyzed 1,2-dicarbonyaltive cyclization system (Scheme 3a), 4-aryl-1-butenes and alkyl bromides constructed a series of α-tetralone and 2,3-dihydroquinolin-4-one through a radical cascade process, constructing four new C–C bonds, and introducing two carbonyl groups and a ring. This reaction has a wide substrate scope and yields the product in moderate to good yields.…”
Section: Carbonylation Reaction Of Alkyl Bromidesmentioning
confidence: 99%
“…The results showed that one carboxyl group of the substrate could form hydrogen bonding interactions with Arg98 and stabilize the binding conformation, which provided an important molecular basis for designing new PPO inhibitors. 1,4-Diketone is a versatile structural backbone found in many pharmaceuticals and bioactive molecules. Studies have proved that the carbonyl groups of the 1,4-diketone moiety of a molecule could form hydrogen bonding interactions with the arginines of the receptor . Herein, in this work, we introduce the bioactive 1,4-diketone group to the backbone of trifludimoxazin, link it to the 5-position of the benzene ring of trifludimoxazin, and generate N -1,4-diketophenyltriazinones I – III (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…3 Radical cyclisation onto the aromatic nucleus to form the desired fused cyclohexanone ring has been reported and represents a complementary approach. 4 However, this last strategy has remained anecdotal because of the inherent limitations of the methods used to generate the radical species. In the present overview, we describe the application of the unique radical chemistry of xanthates to the synthesis of 1-tetralones and naphthalenes, which overcomes most of the shortcomings of the previous routes.…”
Section: Introductionmentioning
confidence: 99%